Polarizing plate, method of manufacturing the same, and optical display device including the same

By forming a barrier layer composed of (meth)acrylate compound, epoxy compound and sulfonamide-based initiator on the polarizing plate, the problem of cracks easily occurring under high temperature and thermal shock conditions is solved, and the low The peeling intensity and yellowing phenomenon improve the durability and handleability of the polarizer.

CN119200070APending Publication Date: 2024-12-27HOARDSUN HENGXIN(WUXI) MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411349598.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-02-01
Filing Date
2018-01-03
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing polarizers are prone to cracks under high temperature and thermal shock conditions, and it is difficult to prevent cracks during peeling. Thiaxonone light enhancer is often used to prevent yellowing.

Method used

Using a barrier layer composed of (meth)acrylate compound, epoxy compound and sulfonamide initiator, a barrier layer is formed by deposition and UV light curing, and is directly formed on the polarizer to ensure a low peeling intensity with the treatment film to facilitate Peel and provide good adhesion at high temperatures.

Benefits of technology

It effectively prevents cracks from occurring under thermal shock conditions of polarizers, reduces the risk of cracks during peeling, and does not require the use of thioxanthone light enhancer to avoid yellowing, while improving the durability and handleability of the polarizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200070A_ABST
    Figure CN119200070A_ABST
Patent Text Reader

Abstract

The present invention provides: a polarizing plate; a method for manufacturing a polarizing plate; and an optical display device including the polarizing plate. The polarizing plate includes an adhesive layer, a barrier layer, a polarizer, and a protective film sequentially stacked in the stated order. The barrier layer is formed directly on the polarizer and is formed of a barrier layer composition including a (meth) acrylate compound, an epoxy compound, and a matte antimony-based initiator. The epoxy compound includes a bifunctional alicyclic epoxy compound. The (meth) acrylate compound includes a hydrophilic (meth) acrylate compound. The barrier layer composition also includes at least one of a monofunctional aromatic epoxy compound and a bifunctional aliphatic epoxy compound.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application of the invention patent application with application number 201880009656.6 filed on January 3, 2018 and invention name “Polarizing plate, method for manufacturing polarizing plate and optical display device comprising the same”. Technical Field

[0002] The present invention relates to a polarizing plate, a method for manufacturing a polarizing plate, and an optical display including the polarizing plate. More specifically, the present invention relates to a polarizing plate including a barrier layer, the barrier layer exhibiting good adhesion to a polarizer and capable of preventing cracks from being generated in the polarizer during thermal shock, and being formed of a barrier layer composition, the barrier layer composition having a low peeling strength relative to a treated film after curing to make the treated film easy to peel off, thereby suppressing cracks from being generated during peeling. Background Art

[0003] In a liquid crystal display, polarizing plates must be provided to both sides of a glass substrate to constitute the surface of a liquid crystal panel for forming an image. The polarizing plate generally includes a transparent protective film formed of a triacetyl cellulose resin and bonded to one or both surfaces of a polarizer composed of a polyvinyl alcohol film and a dichroic material such as iodine and the like via a polyvinyl alcohol adhesive to protect the polarizer. In addition, it becomes difficult to ensure sufficient durability of the polarizing plate, and durability under harsh conditions such as thermal shock under low and high temperature conditions is required (see Japanese Unexamined Patent Publication No. 2006-220732).

[0004] On the other hand, although a polarizing plate including a transparent protective film disposed only on one surface of a polarizer is used in terms of a slim structure, such a polarizing plate includes an adhesive layer formed on the other surface of the polarizer. However, such a thin adhesive type polarizing plate including a transparent protective film disposed only on one surface of a polarizer has poor durability and easily causes cracks in the stretching direction (MD direction) of the polarizer under harsh conditions. In addition, a polarizing plate including a protective layer formed on at least one side of a polarizer for the purpose of reducing thickness is proposed in the art (see Japanese Unexamined Patent Publication No. 2009-122796). Summary of the invention

[0005] Technical issues

[0006] One aspect of the present invention provides a polarizing plate including a barrier layer that exhibits good adhesion to a polarizer and is capable of preventing cracks from being generated in the polarizer upon thermal shock.

[0007] Another aspect of the present invention provides a polarizing plate including a barrier layer exhibiting good adhesion to each of a polarizer and an adhesive layer at a high temperature.

[0008] Another aspect of the present invention provides a polarizing plate including a barrier layer, wherein the barrier layer is formed of a barrier layer composition, and the barrier layer composition has a low peel strength relative to a processing film after curing to facilitate peeling of the processing film, thereby suppressing generation of cracks during peeling.

[0009] Still another aspect of the present invention provides a polarizing plate including a barrier layer, wherein the barrier layer does not require the use of a thioxanthone light enhancer to prevent yellowing.

[0010] Another aspect of the present invention provides a method for manufacturing a polarizing plate, wherein the polarizing plate includes a barrier layer formed of a barrier layer composition having a low peel strength relative to a processing film after curing to facilitate peeling of the processing film and thereby suppress the generation of cracks during peeling.

[0011] Technical Solutions

[0012] According to one aspect of the present invention, a polarizing plate comprises: an adhesive layer, a barrier layer, a polarizer, and a protective film stacked in the stated order, wherein the barrier layer is directly formed on the polarizer and is formed of a barrier layer composition comprising a (meth)acrylate compound, an epoxy compound, and a sulfonium antimony initiator. The epoxy compound comprises a difunctional alicyclic epoxy compound. The (meth)acrylate compound comprises a hydrophilic (meth)acrylate compound. The barrier layer composition also comprises at least one of a monofunctional aromatic epoxy compound and a difunctional aliphatic epoxy compound. The difunctional alicyclic epoxy compound and at least one of the (meth)acrylate compound and the monofunctional aromatic epoxy compound and the difunctional aliphatic epoxy compound are present in a weight ratio of 60 wt % to 90 wt % of the difunctional alicyclic epoxy compound: 10 wt % to 40 wt % of the (meth)acrylate compound and at least one of the monofunctional aromatic epoxy compound and the difunctional aliphatic epoxy compound, based on a total of 100 parts by weight. The difunctional aliphatic epoxy compound is present in an amount of 10 wt % to 40 wt % in terms of solid content in the curable component of the barrier layer composition.

[0013] According to another aspect of the present invention, a method for manufacturing a polarizing plate comprises: depositing a barrier layer composition onto one surface of a polarizer, then attaching a treatment film thereto; and curing the barrier layer composition to form a barrier layer, then peeling off the treatment film from the barrier layer. The barrier layer is formed by a barrier layer composition comprising a (meth)acrylate compound, an epoxy compound, and a sulfonium antimony initiator. The epoxy compound comprises a difunctional alicyclic epoxy compound. The (meth)acrylate compound comprises a hydrophilic (meth)acrylate compound. The barrier layer composition also comprises at least one of a monofunctional aromatic epoxy compound and a difunctional aliphatic epoxy compound. The difunctional alicyclic epoxy compound and at least one of the (meth)acrylate compound and the monofunctional aromatic epoxy compound and the difunctional aliphatic epoxy compound are present in a weight ratio of 60 wt % to 90 wt % of the difunctional alicyclic epoxy compound: 10 wt % to 40 wt % of at least one of the (meth)acrylate compound and the monofunctional aromatic epoxy compound and the difunctional aliphatic epoxy compound, based on 100 parts by weight of the total. The difunctional aliphatic epoxy compound is present in an amount of 10 wt % to 40 wt % in the curable component of the barrier layer composition in terms of solid content. The peel strength between the barrier layer and the treated film is about 40 gf / 25 mm or less.

[0014] According to another aspect of the present invention, an optical display comprises the polarizing plate according to the present invention.

[0015] Beneficial effects

[0016] The present invention provides a polarizing plate including a barrier layer, the barrier layer exhibiting good adhesion to a polarizer and capable of preventing cracks from being generated in the polarizer upon thermal shock.

[0017] The present invention provides a polarizing plate including a barrier layer exhibiting good adhesion to each of a polarizer and an adhesive layer at high temperatures.

[0018] The present invention provides a polarizing plate including a barrier layer, wherein the barrier layer is formed of a barrier layer composition, and the barrier layer composition has a low peeling strength relative to a treated film after curing to facilitate peeling of the treated film, thereby suppressing the generation of cracks during peeling.

[0019] The present invention provides a polarizing plate including a barrier layer, wherein the barrier layer does not require the use of a thioxanthone light enhancer to prevent yellowing.

[0020] The present invention provides a method for manufacturing a polarizing plate, wherein the polarizing plate comprises a barrier layer, wherein the barrier layer is formed of a barrier layer composition, and the barrier layer composition has a low peeling strength relative to a processing film after curing to make the processing film easy to peel off, thereby suppressing the generation of cracks during peeling. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a cross-sectional view of a polarizing plate according to an embodiment of the present invention. DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. It should be understood that the present invention is not limited to the following embodiments and can be implemented in different ways. In addition, it should be understood that the embodiments are provided to enable those skilled in the art to fully disclose and thoroughly understand the present invention. In the accompanying drawings, the thickness or width of various components of each device may be exaggerated for convenience. Throughout the drawings, the same components will be represented by the same reference numerals.

[0023] As used herein, spatially relative terms such as "upper" and "lower" are defined with reference to the accompanying drawings. Thus, it should be understood that "upper" and "lower" are used interchangeably. It should be understood that when a layer is referred to as being "on" another layer, the layer may be formed directly on the other layer, or one or more intervening layers may also be present. Thus, it should be understood that when a layer is referred to as being "directly on" another layer, there are no intervening layers therebetween.

[0024] Herein, the "yellowness index" refers to a value measured according to ASTM D1925.

[0025] Herein, in order to evaluate the peel strength relative to the treatment film after curing the barrier layer composition, a sample was prepared by the following method. A stack of a protective film and a polarizer was prepared, and the barrier layer composition was deposited on one surface of the polarizer, and the treatment film was attached to the barrier layer composition, and then irradiated with UV light under the conditions of 400 mW / cm2 and 1,000 mJ / cm2 to prepare a sample, which was then cut into a size of 25 mm × 150 mm (TD of polarizer × MD of polarizer). The polarizer bonded to the protective film and the treatment film was connected to the upper and lower clamps of a tensile tester (texture analyzer), and the peel strength was measured at 25°C according to a 30 kg force load cell when the treatment film was peeled off at a rate of 5 mm / s.

[0026] Herein, the term "glass transition temperature (Tg) of a homopolymer phase" may refer to a glass transition temperature measured with respect to a homopolymer of a target monomer using DSC Discovery (TA Instrument Inc.). Specifically, a homopolymer of a target monomer is heated to 200°C at a rate of 20°C / min, slowly cooled to -180°C at the same rate, and heated to 200°C at a rate of 10°C / min to obtain an endothermic transition curve. The inflection point of the endothermic transition curve may be determined as the glass transition temperature.

[0027] Herein, the "modulus" of the adhesive layer refers to the storage modulus, as measured on a sample in a dynamic mode (stress 5%, 1 Hz) at 25° C. using an advanced rheometry expansion system (ARES, TA Instruments). Here, to prepare the sample, the adhesive layer composition is coated on a release film (e.g., a polyethylene terephthalate film) and aged at 35° C. and 45% relative humidity (RH) to form a 25 μm thick adhesive film, which is then stacked multiple times to prepare a 0.8 mm thick sample.

[0028] Herein, the term "moisture permeability" is a value measured on the protective layer under the conditions of 40°C and 90% RH for 24 hours according to KS A1013.

[0029] As used herein, the term "(meth)acryl" refers to acryl and / or methacryl.

[0030] In the following, reference will be made to Figure 1 A polarizing plate according to one embodiment of the present invention is described. Figure 1 is a cross-sectional view of a polarizing plate according to an embodiment of the present invention.

[0031] refer to Figure 1 The polarizing plate 100 may include a polarizer 110 , a protective film 120 , a barrier layer 130 , and an adhesive layer 140 .

[0032] In the polarizing plate 100, the protective film 120, the polarizer 110, the barrier layer 130, and the adhesive layer 140 are sequentially stacked in the stated order, and the barrier layer 130 is directly formed on the polarizer 110 and the adhesive layer 140. Herein, the expression "directly formed on" means that another adhesive layer, another bonding layer, or another adhesive / bonding layer is not interposed between the barrier layer and the polarizer.

[0033] The barrier layer 130 may be formed of a barrier layer composition comprising an epoxy compound and a sulfonium antimony-based initiator. The present invention is based on the presence of a barrier layer, which can provide a barrier effect and can exhibit good adhesion to the polarizer, while fully preventing cracks from occurring in the polarizer during thermal shock by containing a sulfonium antimony-based initiator in the barrier layer. Specifically, thermal shock refers to 250 cycles of repetition, wherein 1 cycle refers to a cycle between -40°C and 85°C. The barrier layer exhibits good adhesion to the polarizer at both high and low temperatures, and undergoes a small modulus change to prevent cracks from occurring in the polarizer even during repeated cycles between low and high temperatures. Although it is not clear how the sulfonium antimony-based initiator affects the aforementioned effects of the barrier layer, it is believed that these effects of the barrier layer are obtained by the reaction between sulfonium, antimony, epoxy compounds and (meth)acrylate compounds (but not limited thereto).

[0034] In addition, as described in detail below, the barrier layer 130 is formed by depositing a barrier layer composition onto one surface of the polarizer 110 and attaching a processing film thereto, then curing the barrier layer composition and peeling the processing film therefrom. The processing film is basically used to protect the barrier layer composition while preventing contamination of the barrier layer composition. The processing film can be a non-stretched or stretched polypropylene film or polyethylene terephthalate film, preferably a polyethylene terephthalate film. The barrier layer 130 is formed by a barrier layer composition, which has a low peel strength relative to the processing film after curing to make the processing film easy to peel off, and can prevent cracks from being generated in the polarizer when peeling off the processing film, thereby improving the durability and processability of the polarizer. Specifically, the barrier layer 130 may have a peel strength of about 40 gf / 25 mm or less than 40 gf / 25 mm relative to the processing film. For example, the barrier layer 130 may have a peel strength of about 10 gf / 25 mm to about 40 gf / 25 mm or about 10 gf / 25 mm to about 30 gf / 25 mm. Within this range, the barrier layer can prevent fine cracks from being generated when peeling the processing film, while improving the durability and processability of the polarizing plate.

[0035] The blocking layer 130 is formed on one surface of the polarizer 110 to be disposed at an opposite side with respect to the protective film 120 , and protects the polarizer 110 while blocking external moisture from penetrating into the polarizer 110 , thereby improving durability of the polarizing plate 100 under high temperature and high humidity conditions.

[0036] The barrier layer 130 is formed immediately below the polarizer 110 , exhibits good adhesion to the polarizer 110 , and provides good durability without a separate protective film between the polarizer 110 and the adhesive layer 140 , thereby reducing the thickness of the polarizing plate 100 .

[0037] The barrier layer 130 may be formed on the other surface of the polarizer 110 at the opposite side of the protective film 120 to suppress the warping of the polarizing plate 100. Specifically, the thickness ratio of the protective film to the barrier layer may be in the range of about 5:1 to about 100:1. Specifically, the thickness ratio of the protective film to the barrier layer may be in the range of about 10:1 to about 50:1, more specifically about 10:1 to about 30:1. Within this thickness range, the warping of the polarizing plate can be suppressed.

[0038] The barrier layer 130 may have a thickness of about 20 micrometers or less, specifically about 1 micrometer to about 15 micrometers, more specifically about 2 micrometers to about 10 micrometers, for example about 2 micrometers to about 5 micrometers. Within this range, the barrier layer can be used for the polarizing plate and has a suitable thickness compared to the protective film, thereby suppressing the warping of the polarizing plate and improving its barrier effect.

[0039] The barrier layer 130 may have a glass transition temperature of about 90° C. or greater, for example, about 90° C. to about 150° C. or about 90° C. to about 120° C. Within this range, the barrier layer exhibits good adhesion to the polarizer and exhibits a smaller modulus change due to temperature change to suppress shrinkage / expansion of the polarizer.

[0040] The blocking layer 130 has a yellow index of about 1.0 or less, for example, about 0.1 to about 1.0. Within this range, the blocking layer does not appear yellow and thus can be used in a polarizing plate.

[0041] The barrier layer 130 is formed of a barrier layer composition including an epoxy compound and a sulfonium antimony-based initiator, and can be formed by curing via actinic radiation (including UV radiation, electron beams, and the like). The barrier layer composition may further include a (meth)acrylate compound. The epoxy compound and the (meth)acrylate compound as a whole form a curable component.

[0042] The epoxy compound may include at least one of an alicyclic epoxy compound, an aromatic epoxy compound, and an aliphatic epoxy compound.

[0043] In one embodiment, the epoxy compounds may be exclusively alicyclic epoxy compounds.

[0044] In another embodiment, the epoxy compound may include a mixture of an alicyclic epoxy compound and at least one of an aliphatic epoxy compound and an aromatic epoxy compound. For example, the epoxy compound may include a mixture of a difunctional alicyclic epoxy compound and a difunctional aliphatic epoxy compound. For example, the epoxy compound may include a mixture of a difunctional alicyclic epoxy compound and a monofunctional aromatic epoxy compound.

[0045] The alicyclic epoxy compound may have a glass transition temperature of about 180° C., for example, about 180° C. to about 200° C. in a homopolymer phase. As such, the alicyclic epoxy compound is an epoxy compound having a high glass transition temperature, and may improve crack resistance and adhesion to a polarizer.

[0046] The alicyclic epoxy compound may include at least one selected from the following: 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, 2-(3,4-epoxycyclohexyl-5,5-spiro-3,4-epoxy)cyclohexane-m-dioxane, bis(3,4-epoxycyclohexylmethyl)adipate, bis(3,4-epoxy-6-methylcyclohexyl)adipate, 3,4-epoxy-6-methylcyclohexyl-3',4'-epoxy-6'-methylcyclohexanecarboxylate, ε-caprolactone-modified 3,4-epoxycyclohexylmethyl -3',4'-epoxycyclohexanecarboxylate, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate modified with trimethyl caprolactone, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate modified with β-methyl-δ-valerolactone, methylenebis(3,4-epoxycyclohexane), di(3,4-epoxycyclohexylmethyl)ether of ethylene glycol, ethylenebis(3,4-epoxycyclohexanecarboxylate), epoxycyclohexahydrophthalic acid dioctyl and epoxycyclohexahydrophthalic acid di-2-ethylhexyl. CELLOXIDE 2021P (DAICEL Co., Ltd.) can be used as the alicyclic epoxy compound, but is not limited thereto.

[0047] The alicyclic epoxy compound may be present in an amount of about 40 wt % to about 90 wt % in the curable component of the barrier layer composition in terms of solid content. Specifically, the alicyclic epoxy compound may be present in an amount of about 50 wt % to about 90 wt % or about 50 wt % to about 85 wt %. Within this range, the barrier layer composition may exhibit good adhesion to the polarizer and have a low viscosity to provide good coatability.

[0048] The alicyclic epoxy compound may be present in the epoxy resin composition in an amount of about 70 wt % to about 100 wt %, specifically about 70 wt % to about 90 wt % or about 100 wt % in terms of solid content. Within this range, the barrier layer composition has a high glass transition temperature to provide a barrier effect.

[0049] The aliphatic epoxy compound may be used as a diluent solvent to prevent the coating property from being reduced due to the high viscosity of the alicyclic epoxy compound. The aliphatic epoxy compound may include at least one selected from a monofunctional aliphatic epoxy compound and a difunctional aliphatic epoxy compound. The monofunctional aliphatic epoxy compound may include at least one selected from ethyl glycidyl ether, butyl glycidyl ether, hexyl glycidyl ether, octyl glycidyl ether, 2-ethylhexyl glycidyl ether, dodecyl glycidyl ether, and octadecyl glycidyl ether. The difunctional aliphatic epoxy compound may include at least one selected from the following: 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether; diglycidyl ether of polyether polyol, obtained by adding at least one alkylene oxide to aliphatic polyvalent alcohols such as ethylene glycol, propylene glycol, glycerol and the like; diglycidyl ester of aliphatic long chain dibasic acid; diglycidyl ether of aliphatic higher alcohol; and diglycidyl ether of higher fatty acid. The aliphatic epoxy compound may further include a trifunctional aliphatic epoxy compound or a higher functional aliphatic epoxy compound. Preferably, the aliphatic epoxy compound may be a difunctional aliphatic epoxy compound.

[0050] The aliphatic epoxy compound may be optionally present in the curable component of the barrier layer composition in an amount of about 60 wt % or less, specifically about 5 wt % to about 50 wt %, about 5 wt % to about 40 wt %, about 15 wt % to about 50 wt %, about 10 wt % to about 60 wt %, about 10 wt % to about 50 wt %, or about 10 wt % to about 40 wt % in terms of solid content. Within this range, the barrier layer composition can exhibit good adhesion to the polarizer and does not have high viscosity to ensure good coatability.

[0051] The aromatic epoxy compound may include at least one selected from the following: a monofunctional aromatic epoxy compound such as phenyl glycidyl ether, cresyl glycidyl ether and the like; bisphenol A, bisphenol F; and phenol novolac, cresol novolac, bisphenol A novolac, dichloropentadiene novolac, glycidyl ether of trisphenol methane, triglycidyl p-aminophenol and tetraglycidyl methylene dianiline. Preferably, the aromatic epoxy compound is a monofunctional aromatic epoxy compound.

[0052] The aromatic epoxy compound may be optionally present in an amount of about 30 wt % or less, about 1 wt % to about 30 wt %, specifically about 1 wt % to about 20 wt % in terms of solid content in the curable component of the barrier layer composition. Within this range, the barrier layer composition can exhibit good adhesion to the polarizer and does not have high viscosity to ensure good coatability.

[0053] The epoxy compound may be present in the curable component of the barrier layer composition in an amount of about 40 wt % to about 100 wt %, specifically about 40 wt % to about 90 wt %, about 50 wt % to about 85 wt %, about 60 wt % to about 90 wt %, or about 100 wt % in terms of solid content. Within this range, the barrier layer composition may exhibit good adhesion to the polarizer and does not have high viscosity to ensure good coatability.

[0054] In the barrier layer composition, the (meth)acrylate compound can reduce the viscosity of the barrier layer composition to improve the coatability of the barrier layer composition, increase the hardness of the barrier layer, and promote the curing of the barrier layer composition. The (meth)acrylate compound can trigger a free radical reaction by light energy.

[0055] The (meth)acrylate compound may include at least one selected from hydrophilic (meth)acrylates and hydrophobic (meth)acrylates.

[0056] The hydrophilic (meth)acrylate is a (meth)acrylate having a hydroxyl group as a hydrophilic group, and initiates free radical polymerization by light energy to stably react by light energy without being inhibited by the reaction of moisture of the polarizer. The hydrophilic (meth)acrylate may include a C1 to C2-containing acrylate having at least one hydroxyl group. 10 The hydrophilic (meth)acrylate may have a monofunctional group or a difunctional group or a higher functional group. For example, the hydrophilic (meth)acrylate may include at least one selected from the following: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate or 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and 2-hydroxy-3-phenoxypropyl (meth)acrylate.

[0057] The hydrophilic (meth)acrylate may be present in the curable component of the barrier layer composition in an amount of about 60 wt % or less, specifically about 1 wt % to about 40 wt %, about 10 wt % to about 60 wt %, about 10 wt % to about 50 wt %, about 15 wt % to about 50 wt %, or about 10 wt % to about 40 wt % in terms of solid content. Within this range, the barrier layer composition can improve adhesion between the polarizer and the barrier layer.

[0058] The hydrophobic (meth)acrylate may include other (meth)acrylates in addition to the hydrophilic (meth)acrylate. The hydrophobic (meth)acrylate may include a monofunctional (meth)acrylic compound having one (meth)acryloyloxy group, a difunctional (meth)acrylic compound having two (meth)acryloyloxy groups, an oligomer thereof, or a mixture thereof.

[0059] The monofunctional (meth) acrylic compound may include an unsubstituted C1 to C 10 Alkyl (meth)acrylate, having C3 to C 10 Alicyclic (meth)acrylate, with C6 to C 20 Aromatic (meth)acrylate or having C7 to C 20 (Meth)acrylate of aralkyl. Specifically, the monofunctional (meth)acrylic compound may include at least one selected from the following: tert-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, phenoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate and benzyl (meth)acrylate. In addition, the monofunctional (meth)acrylic compound may include at least one selected from the following: tetrahydrofuran methyl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, ethyl carbitol (meth)acrylate, trimethylolpropane mono(meth)acrylate, pentaerythritol mono(meth)acrylate and phenoxy polyethylene glycol mono(meth)acrylate.

[0060] The difunctional (meth)acrylic compound may include at least one selected from the following: unsubstituted alkylene glycol di(meth)acrylate, polyoxyalkylene glycol di(meth)acrylate, halogenated alkylene glycol di(meth)acrylate, di(meth)acrylate of aliphatic polyol, di(meth)acrylate of hydrogenated dicyclopentadiene or tricyclodecane diol, di(meth)acrylate of dioxane diol or dioxane diol, bisphenol A or bisphenol F di(meth)acrylate with alkylene oxide adduct, and epoxy di(meth)acrylate of bisphenol A or bisphenol F. Specifically, the bifunctional (meth) acrylic compound may include at least one selected from the following: ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and dipropylene glycol di(meth)acrylate. (Meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polybutylene glycol di(meth)acrylate, silicone di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane, 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane, hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 1,3-dioxane-2,5-diyl di(meth)acrylate and tris(hydroxyethyl)isocyanurate di(meth)acrylate.

[0061] The hydrophobic (meth)acrylate may be present in an amount of about 30 wt % or less, specifically about 0.1 wt % to about 30 wt %, more specifically about 0.1 wt % to about 10 wt % in terms of solid content in the curable component of the barrier layer composition. Within this range, the barrier layer composition can improve the adhesion between the polarizer and the barrier layer.

[0062] The (meth)acrylate compound may be optionally present in an amount of about 60 wt % or less, specifically about 10 wt % to about 60 wt %, about 15 wt % to about 50 wt %, or about 10 wt % to about 40 wt % in terms of solid content in the curable component of the barrier layer composition. Within this range, the barrier layer composition can exhibit good adhesion to the polarizer and does not have high viscosity to ensure good coatability.

[0063] The epoxy compound and the (meth)acrylate compound may be present in a weight ratio of about 60 wt % to about 90 wt %: about 10 wt % to about 40 wt % (epoxy compound: (meth)acrylate compound) in a total of 100 wt %. Within this range, the barrier layer composition can ensure a high glass transition temperature of the barrier layer to provide a barrier effect while maintaining a low viscosity for good coatability.

[0064] In one embodiment, the barrier layer composition may include a difunctional alicyclic epoxy compound; and at least one selected from a monofunctional aromatic epoxy compound, a difunctional aliphatic epoxy compound, and a (meth)acrylate compound. Here, the difunctional alicyclic epoxy compound and at least one selected from a monofunctional aromatic epoxy compound, a difunctional aliphatic epoxy compound, and a (meth)acrylate compound may be present in a weight ratio of about 60 wt % to about 90 wt %: about 10 wt % to about 40 wt %. Within this range, the barrier layer composition may ensure a high glass transition temperature of the barrier layer to provide a barrier effect while maintaining a low viscosity for good coatability.

[0065] The sulfonium antimony type initiator can cure the curable component.

[0066] The sulfonium antimony initiator may be contained in an epoxy compound or in a mixture of an epoxy compound and a (meth) acrylate compound to cure the curable component without using a thioxanthone light enhancer, thereby forming a barrier layer that does not suffer from yellowing. The sulfonium antimony initiator may be contained in an epoxy compound or in a mixture of an epoxy compound and a (meth) acrylate compound to improve the adhesion to the polarizer, thereby preventing cracks from being generated in the barrier layer due to thermal shock. As described below, the degree of crack generation in the polarizer may vary depending on the adhesion to the polarizer even under the same thermal shock conditions. In addition, the sulfonium antimony initiator may be contained in an epoxy compound or in a mixture of an epoxy compound and a (meth) acrylate compound so that the barrier layer composition exhibits a low peel strength relative to the treated film after curing, so that the treated film is easy to peel off, thereby suppressing the generation of cracks during peeling.

[0067] Sulfonium antimony initiators are photocationic initiators and are composed of sulfonium cations and antimony anions. Examples of cations may include triarylsulfonium, such as triphenylsulfonium, diphenyl-4-thiophenoxyphenylsulfonium, and diphenyl-4-phenylthienylsulfonium; bis[4-(diphenyldihydrosulfanyl)phenyl]sulfide; and similar cations. Examples of anions may include hexafluoroantimonate (SbF6 - ), hexachloroantimonate (SbCl6 - ) and similar anions. Preferably, the sulfonium antimony initiator is diphenyl-4-phenylthienylsulfonium hexafluoroantimonate.

[0068] The sulfonium antimony initiator may be present in an amount of about 0.1 to about 10 parts by weight based on a total of 100 parts by weight of the curable components of the barrier layer composition in terms of solid content. Specifically, the sulfonium antimony initiator may be present in an amount of about 0.5 to about 5 parts by weight, for example, about 0.5 to about 3 parts by weight. Within this range, the initiator may allow sufficient curing of the curable components, may prevent a reduction in the transparency of the barrier layer due to residual initiator, and may prevent cracks from being generated in the polarizer.

[0069] The barrier layer composition may further include a photoradical initiator. The photoradical initiator may further increase the curing rate of the (meth)acrylate compound. The photoradical initiator may include at least one selected from phosphorus, triazine, acetophenone, benzophenone, benzoin, oxime and phenyl ketone initiators. The photoradical initiator may be present in an amount of about 0.1 to about 10 parts by weight based on a total of 100 parts by weight of the barrier layer composition curable components in terms of solid content. Specifically, the photoradical initiator may be present in an amount of about 1 to about 6 parts by weight. Within this range, the initiator may allow sufficient curing of the curable components and prevent the barrier layer transparency from being reduced due to residual initiators.

[0070] The barrier layer composition may be a composition without a solvent, or may further contain a solvent to improve coatability, applicability or processability. The solvent may include methyl ethyl ketone, methyl isobutyl ketone and propylene glycol monomethyl ether acetate, but is not limited thereto.

[0071] The barrier layer composition may further include additives. The additives may provide additional functions for the barrier layer. Specifically, the additives may include at least one selected from the following: UV absorbers, reaction inhibitors, adhesion promoters, thixotropic agents, conductivity imparting agents, color regulators, stabilizers, antistatic agents, antioxidants, and leveling agents, but are not limited thereto.

[0072] The barrier layer composition may further include fine particles to further improve the hardness and mechanical strength of the barrier layer. Specifically, the fine particles include hygroscopic fine particles to further improve the moisture barrier effect of the barrier layer. The fine particles may include at least one of silicon dioxide, aluminum oxide, zirconium oxide and titanium oxide, but are not limited thereto. The fine particles may be partially or completely surface treated with epoxy, (meth) acrylate or vinyl groups to improve compatibility. The fine particles may have any shape and any size without specific restrictions. Specifically, the fine particles may include spherical particles, flaky particles, amorphous particles and similar particles. The fine particles may have an average particle size of about 1 nanometer to about 200 nanometers, specifically about 8 nanometers to about 50 nanometers. Within this range, the fine particles can increase the hardness of the barrier layer without affecting the surface roughness and transparency of the barrier layer. The fine particles may be present in the barrier layer composition in an amount of about 3 weight % to about 30 weight %, specifically about 5 weight % to about 20 weight %. Within this range, the fine particles can increase the hardness of the barrier layer without affecting the surface roughness and transparency of the barrier layer.

[0073] The barrier layer composition may have a viscosity of about 5 centipoise to about 200 centipoise, specifically about 10 centipoise to about 150 centipoise at 25° C. Within this range, the barrier layer composition may easily form a barrier layer.

[0074] The polarizer 110 is formed between the barrier layer 130 and the adhesive layer 140 to polarize external light entering the polarizing plate 100 .

[0075] Polarizer 110 may include a polarizer formed of a polyvinyl alcohol film. In one embodiment, the polarizer may include a polyvinyl alcohol film dyed with at least one of iodine or dichroic dyes, or a polyene polarizer obtained by dehydrating a polyvinyl alcohol film. The polyvinyl alcohol film may have a saponification degree of about 85 mol % to about 100 mol %, specifically about 98 mol % to about 100 mol %. The polyvinyl alcohol film may have a degree of polymerization of about 1,000 to about 10,000, specifically about 1,500 to about 10,000. The polyvinyl alcohol film may have a thickness of about 50 microns to about 200 microns. Within these saponification degrees, polymerization degrees, and thickness ranges, polarizers can be manufactured. Specifically, a polyvinyl alcohol-based polarizer can be manufactured by dyeing a polyvinyl alcohol film with at least one of iodine or dichroic dyes, and then uniaxially stretching the polyvinyl alcohol film to a final elongation of 2 to 8 times, specifically 3 to 6 times, of its initial length in the longitudinal direction (MD, machine direction). Stretching may include dry stretching, wet stretching, or a combination thereof. Herein, "final elongation" refers to the ratio of the final length of the polyvinyl alcohol polarizer to the initial length of the polyvinyl alcohol film. The polyvinyl alcohol polarizer may be immersed in a boric acid solution or in a potassium iodide solution for color correction after stretching. Specifically, a polyene polarizer may be manufactured by applying an acid catalyst to a polyvinyl alcohol film for dehydration, followed by drying. The acid catalyst may include: an organic acid, including an aromatic sulfonic acid, such as toluenesulfonic acid including p-toluenesulfonic acid and the like; an inorganic acid; or a mixture thereof.

[0076] The polarizer 110 may have a thickness of about 5 micrometers to about 100 micrometers, specifically about 5 micrometers to about 50 micrometers. Within this range, the polarizer may be used for a polarizing plate.

[0077] The protective film 120 is formed on one surface of the polarizer 110 to protect the polarizer 110. The protective film 120 may be formed on one surface of the polarizer 110 via the bonding layer 130.

[0078] The protective film 120 has good moisture permeability resistance and can have a moisture permeability of about 30 g / m2·24 hours or less, specifically about 1 g / m2·24 hours to about 25 g / m2·24 hours, more specifically about 5 g / m2·24 hours to about 15 g / m2·24 hours. Within this range, the protective film can block external moisture from entering the polarizer, thereby improving the durability of the polarizer under high temperature / humidity conditions.

[0079] In one embodiment, the protective film 120 may have an in-plane retardation (Re) of about 5,000 nm or more, specifically about 5,000 nm to about 15,000 nm at a wavelength of 550 nm, as calculated by Equation 1. More specifically, the protective film 120 has an in-plane retardation (Re) of about 6,000 nm to about 12,000 nm. Within this range, the polarizing plate can prevent the generation of rainbow spots.

[0080] <Equation 1>

[0081] Re=(nx-ny)×d,

[0082] Wherein nx and ny are the refractive indices of the protective film in the x-axis and y-axis directions of the protective film at a wavelength of 550 nanometers, respectively, and d is the thickness of the protective film (unit: nanometer).

[0083] The protective film 120 may have a biaxiality (NZ) of about 1.8 or less, specifically about 1.0 to about 1.8 at a wavelength of 550 nanometers, as calculated by Equation 2, and an out-of-plane retardation (Rth) of 15,000 nanometers or less, specifically 6,000 nanometers to 12,000 nanometers at a wavelength of 550 nanometers, as calculated by Equation 3. Within this range, the polarizing plate can prevent the generation of rainbow spots due to birefringence.

[0084] <Equation 2>

[0085] NZ=(nx-nz) / (nx-ny)

[0086] <Equation 3>

[0087] Rth=((nx+ny) / 2-nz)×d

[0088] Wherein nx, ny and nz are the refractive indices of the protective film in the x-axis, y-axis and z-axis directions of the protective film at a wavelength of 550 nanometers, and d is the thickness of the protective film (unit: nanometer).

[0089] In another embodiment, the protective film 120 may have an in-plane retardation (Re) of about 500 nanometers or less, such as about 350 nanometers or less, at a wavelength of 550 nanometers, as calculated by Equation 1. The protective film 120 may have a biaxiality (NZ) of about 10 or more, such as about 15 or more, at a wavelength of 550 nanometers, as calculated by Equation 2. The protective film 120 may have an out-of-plane retardation (Rth) of about 6,000 nanometers or more, such as about 6,500 nanometers or more, at a wavelength of 550 nanometers, as calculated by Equation 3.

[0090] The protective film 120 may be formed of a polyester resin and may include an optically transparent film. Specifically, the polyester resin may include at least one selected from the following: polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, and polybutylene naphthalate, but is not limited thereto. In one embodiment, the protective film 120 may be formed of one type of polyester resin and may be composed of a single layer. The protective film 120 composed of a single layer has the moisture permeability as described above, thereby improving the durability of the polarizing plate under high temperature / humidity conditions.

[0091] The protective film 120 has a thickness of about 5 μm to about 200 μm, specifically about 10 μm to about 150 μm, more specifically about 50 μm to about 120 μm. Within this range, the protective film can be used for the polarizing plate and can suppress warping of the polarizing plate together with the barrier layer.

[0092] The protective film 120 may further include typical additives in addition to the resin for the protective film. Specifically, the additives may include a UV absorber, a leveler, an antistatic agent, and the like. The UV absorber may include a typical UV absorber capable of absorbing light having a wavelength of 200 nanometers to 400 nanometers. Specifically, the UV absorber may include at least one selected from the following: a phenol UV absorber, a benzotriazole UV absorber, a salicylic acid UV absorber, a triazine UV absorber, and an oxamide UV adsorbent.

[0093] The protective film 120 is a film uniaxially stretched in TD or a film biaxially stretched in TD and MD, and the polarizer 110 is a film uniaxially stretched in MD, as described above. In the polarizing plate 100, the TD of the protective film 120 may be substantially orthogonal to the MD of the polarizer 110. Therefore, it is possible to prevent the warping of the polarizing plate 100. Herein, the expression "substantially orthogonal" may include a structure in which the TD of the protective layer is orthogonal to the MD of the polarizer not only at an angle of 90° but also at an angle within an acceptable tolerance of 90°.

[0094] Although Figure 1 Although not shown in the figure, the protective film 120 further includes a functional coating on one surface thereof to provide additional functions to the polarizing plate. Specifically, the functional coating may include at least one selected from the following: a hard coating, an anti-reflection layer, an anti-fingerprint layer, an anti-static layer, and a low-reflection layer, but is not limited thereto. The functional coating may have a thickness of about 1 micron to about 100 microns, specifically about 1 micron to about 50 microns, and more specifically about 1 micron to about 20 microns. Within this thickness range, the functional coating can provide additional functions to the polarizing plate without affecting the protective film, and can be used for the polarizing plate.

[0095] Although Figure 1Although not shown in the figure, the protective film 120 may further include a primer layer on the other surface of the protective film 120 to allow further improvement of the bonding between the polarizer 110 and the protective film 120 via the bonding layer. The primer layer may become a hydrophilic surface modification layer. The primer layer may be formed by applying a composition comprising a resin for the primer layer, the resin having both a hydrophilic group and a hydrophobic group. For example, the resin for the primer layer may include at least one of a polyester resin and a polyvinyl acetate resin. The primer layer may have a thickness of about 1 nanometer to about 100 nanometers, specifically about 1 nanometer to about 50 nanometers, and more specifically about 1 nanometer to about 20 nanometers. Within this range, the primer layer can ensure good adhesion to the polarizer and a high total light transmittance.

[0096] The adhesive layer 140 attaches the polarizing plate 100 to a liquid crystal panel, an organic light emitting panel, and the like.

[0097] The adhesive layer 140 may have a modulus of about 0.1 MPa or less, specifically about 0.001 MPa to about 0.1 MPa at 23° C. Within this range, the adhesive layer may minimize warping of the polarizing plate when the protective layer, the polarizer, and the barrier layer are stacked, and may release stress of the polarizer, thereby providing good crack resistance.

[0098] The adhesive layer 140 may have a thickness of about 5 to 40 micrometers, specifically about 10 to 30 micrometers. Within this range, the adhesive layer can be used for a polarizing plate.

[0099] The adhesive layer 140 may be formed of an adhesive layer composition, the adhesive layer composition comprising a (meth)acrylic acid copolymer and a crosslinking agent. The adhesive layer composition may comprise a (meth)acrylic acid copolymer and a crosslinking agent of a monomer mixture, the monomer mixture comprising an alkyl-containing (meth)acrylic acid monomer and a hydroxyl-containing (meth)acrylic acid monomer. The alkyl-containing (meth)acrylic acid monomer may comprise an unsubstituted C1 to C 20 Specifically, the alkyl-containing (meth)acrylic acid monomer may include at least one selected from the group consisting of methyl (meth)acrylate, N-butyl (meth)acrylate, pentyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These alkyl-containing (meth)acrylic acid monomers may be used alone or in combination. The hydroxyl-containing (meth)acrylic acid monomer may include a C1 to C2-containing monomer having at least one hydroxyl group. 20 Specifically, the hydroxyl-containing (meth)acrylic acid monomer may include at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. These hydroxyl-containing (meth)acrylic acid monomers may be used alone or in combination.

[0100] The monomer mixture may be present in an amount of about 90 to about 99 parts by weight of an alkyl-containing (meth) acrylic monomer and about 1 to about 10 parts by weight of a hydroxyl-containing (meth) acrylic monomer in terms of solid content. Within this monomer mixture range, the adhesive composition may exhibit high adhesion to the barrier layer and the liquid crystal glass. The crosslinking agent may include a typical isocyanate crosslinking agent. Specifically, the crosslinking agent may include at least one selected from the following: hexamethylene diisocyanate, toluene diisocyanate, xylene diisocyanate, isophorone diisocyanate, naphthalene diisocyanate, and an adduct of toluene diisocyanate modified by trimethylolpropane. The crosslinking agent may be present in an amount of about 0.1 to about 1 parts by weight per 100 parts by weight of the (meth) acrylic copolymer agent. Within this range, the adhesive composition may be fully crosslinked, thereby exhibiting an adhesive effect. The adhesive composition may further include at least one of a silane coupling agent and a crosslinking catalyst.

[0101] The polarizing plate 100 may have a transmittance variation rate of about 3% or less, specifically about 0% to about 3.0%, as calculated by Equation 4. Within this range, the polarizing plate may exhibit good durability under high temperature / humidity conditions and may be used in optical displays.

[0102] <Equation 4>

[0103] Transmittance change rate = |T0-T 500 | / T0×100

[0104] Where T0 is the initial transmittance of the polarizer at a wavelength of 400 nm to 700 nm, and T 500 It is the light transmittance of the polarizing plate at a wavelength of 400 nm to 700 nm as measured after the polarizing plate is allowed to stand at 85° C. and 85% RH for 500 hours and then allowed to stand at 25° C. for 1 hour.

[0105] The polarizing plate 100 may have a polarization degree change rate of about 5% or less, specifically about 0% to about 3%, as calculated by Equation 5. Within this range, the polarizing plate may exhibit good durability under high temperature / humidity conditions and may be used in optical displays.

[0106] <Equation 5>

[0107] Polarization change rate = |P0-P 500 | / P0×100

[0108] Where P0 is the initial polarization of the polarizer, and P 500 It is the degree of polarization of the polarizing plate as measured after the polarizing plate is allowed to stand at 85° C. and 85% RH for 500 hours and then allowed to stand at 25° C. for 1 hour.

[0109] The polarizing plate 100 may have a thickness of about 150 micrometers or less, specifically about 140 micrometers or less, more specifically about 130 micrometers or less. For example, the polarizing plate 100 may have a thickness of about 50 micrometers to about 150 micrometers. Within this range, the polarizing plate can be used in an optical display.

[0110] The polarizing plate 100 may have a light transmittance of about 30% or more, specifically about 30% to about 50%, more specifically about 40% to about 50%, at a wavelength of about 400 nanometers to about 700 nanometers.

[0111] The polarizing plate 100 may have a polarization degree of about 90% or more, specifically, about 95.000% to about 99.990%. Within these ranges of transmittance and polarization degree, the polarizing plate may be used for an optical display.

[0112] Next, a method of manufacturing a polarizing plate according to one embodiment of the present invention will be described.

[0113] A method for manufacturing a polarizing plate according to one embodiment of the present invention includes: depositing a barrier layer composition onto one surface of a polarizer, and then attaching a treatment film thereto; and curing the barrier layer composition to form a barrier layer, and then peeling the treatment film from the barrier layer, wherein the peel strength between the barrier layer and the treatment film is about 40 gf / 25 mm or less.

[0114] The barrier layer composition can be deposited onto the polarizer by a typical deposition method. Specifically, the composition can be deposited by die coating, gravure coating, or the like. Curing can include irradiation with actinic radiation (specifically, UV light) at about 100 mW / cm2 to about 2,000 mW / cm2 and about 100 mJ / cm2 to about 1,000 mJ / cm2. According to the present invention, the barrier layer has a low peel strength relative to the treatment film after the barrier layer composition is cured, so that the treatment film is easy to peel off, thereby suppressing the generation of cracks in the barrier layer during peeling.

[0115] The method may further include depositing an adhesive layer composition onto one surface of the protective film and attaching the protective film to the other surface of the polarizer, and then curing the adhesive layer composition. Here, the deposition and curing may be performed as described above.

[0116] The method may further include depositing an adhesive layer composition onto the barrier layer after stripping the treatment film, followed by aging.

[0117] An optical display according to one embodiment of the present invention may include a polarizing plate according to an embodiment of the present invention. The optical display may include a liquid crystal display and an organic light emitting diode display, but is not limited thereto.

[0118] In a liquid crystal display, the liquid crystal panel may include liquid crystals driven in an in-plane switching (IPS) mode, a twist nematic (TN) mode, a vertical alignment (VA) mode, a patterned vertical alignment (PVA) mode, or a super-patterned vertical alignment (S-PVA) mode.

[0119] Example

[0120] Hereinafter, the present invention will be described in more detail with reference to some examples. It should be understood that these examples are provided for illustration only and should not be understood in any way as limiting the present invention.

[0121] Details of the components used in Examples and Comparative Examples are as follows.

[0122] (A) Epoxy compounds:

[0123] (A1) Alicyclic epoxy resin: 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylic acid (CELLOXIDE 2021P, Daicel)

[0124] (A2) Monofunctional aromatic epoxy resin: phenyl glycidyl ether (EX-141, Nagase)

[0125] (A3) Bifunctional aliphatic epoxy resin: 1,4-butanediol diglycidyl ether (EX-214L, Nagase)

[0126] (B) (Meth)acrylate compounds:

[0127] (B1) Hydrophilic acrylate: 4-hydroxybutyl acrylate (4HBA, Kojin)

[0128] (B2) Hydrophobic acrylate: 2-phenoxyethyl acrylate (M140, Miwon Commercial Co., Ltd.)

[0129] (C) Initiator:

[0130] (C1) Sulfonium antimony initiator (photocationic initiator): diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate (CPI-101A, San-APRO)

[0131] (C2) Iodine initiator (photocationic initiator): (4-methylphenyl) [4- (2-methylpropyl) phenyl] iodonium hexafluorophosphate (Irgacure 250, BASF)

[0132] (C3) Sulfonium phosphate initiator (photocationic initiator): diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P, San-APRO)

[0133] (C4) Photoradical initiator: YANGGACO-184 (BASF)

[0134] (D) Light enhancer: 2,4-diethylthioxanthone (DETX-s, Nipponkayaku) as a thioxanthone light enhancer

[0135] (E) Treatment membrane

[0136] PET treated film: XD510P (Toray Advanced Materials)

[0137] (F) Protective film: Polyethylene terephthalate film (thickness: 80 microns)

[0138] Example 1

[0139] (1) Preparation of polarizer

[0140] A polyvinyl alcohol film (saponification degree: 99.5 mol%, polarization degree: 2,000, thickness: 80 μm) was immersed and dyed in a 0.3% iodine solution. The dyed film was uniaxially stretched to a length 5.0 times its initial length. The stretched polyvinyl alcohol film was immersed in a 3% boric acid solution and a 2% potassium iodide solution for color correction. Subsequently, the polyvinyl alcohol film was dried at 50° C. for 4 minutes to provide a 23 μm thick polarizer.

[0141] (2) Preparation of barrier layer composition

[0142] The weights of the epoxy compound, the (meth)acrylate compound, and the photoinitiator are as listed in Table 1, and the epoxy compound, the (meth)acrylate compound, and the photoinitiator are mixed to prepare a barrier layer composition.

[0143] (3) Preparation of polarizing plate

[0144] A polarizing plate is prepared at 22°C to 25°C and 20% RH to 60% RH. The prepared adhesive layer composition is deposited on one surface of the protective film to form a bonding layer, and then the bonding layer is bonded to one surface of the polarizer. The prepared barrier layer composition is deposited on the other surface of the polarizer, and then the treatment film is attached to the barrier layer composition. Here, the adhesive layer composition is a photocurable adhesive layer composition containing an epoxy compound, a (meth)acrylate compound, and an initiator.

[0145] The barrier layer composition was irradiated with UV light at 400 mW / cm2 and 1,000 mJ / cm2 using a metal halide lamp, and then the treatment film was removed. The adhesive layer composition was deposited on one surface of the barrier layer from which the treatment film was removed, and then aged to prepare a polarizing plate in which an adhesive layer (thickness: 25 microns), a barrier layer (thickness: 3 microns), a polarizer (thickness: 23 microns), a bonding layer (thickness: 3 microns), and a protective film (thickness: 80 microns) were stacked in the stated order. The adhesive layer composition included an acrylic copolymer and an initiator, and the acrylic copolymer included 99 parts by weight of butyl acrylate and 1 part by weight of 4-hydroxybutyl acrylate.

[0146] Example 2 and Example 3

[0147] Each polarizing plate was prepared in the same manner as in Example 1, except that the components and / or content of the barrier layer composition were changed as listed in Table 1.

[0148] Comparative Examples 1 to 6

[0149] Each polarizing plate was prepared in the same manner as in Example 1, except that the components and / or content of the barrier layer composition were changed as listed in Table 1.

[0150] Table 1 shows the components of polarizing plates prepared in Examples and Comparative Examples.

[0151] [Table 1]

[0152]

[0153] The barrier layers and polarizing plates of Examples and Comparative Examples were evaluated in terms of the properties shown in Table 2.

[0154] (1) Adhesion: The cutter was inserted at its tip between the barrier layer and the polarizer at one end of the polarizer. A polarizer that did not allow the cutter tip to be inserted between the barrier layer and the polarizer was rated as ◎; a polarizer that allowed the cutter tip to be slightly inserted therebetween was rated as O; a polarizer that although the cutter tip was slightly inserted between the barrier layer and the polarizer, the barrier layer was torn due to its certain strength during the insertion of the cutter was rated as Δ; and a polarizer that allowed the cutter tip to be easily inserted was rated as X.

[0155] (2) Peel strength: The prepared adhesive layer composition is coated on one surface of the protective film and bonded to one surface of the prepared polarizer. In addition, the prepared barrier layer composition is coated on the other surface of the polarizer and attached to the processing film. The resulting product is irradiated with UV light at 400 mW / cm2 and 1,000 mJ / cm2 using a metal halide lamp to prepare a sample. The sample is cut into a size of 25 mm × 150 mm (TD of polarizer × MD of polarizer) to prepare a sample for peel strength measurement. The polarizer bonded to the protective film and the processing film is connected to the upper and lower clamps of the tensile tester (texture analyzer), and the peel strength is measured at 25°C according to a 30 kg force dynamometer when peeled at a rate of 5 mm / s.

[0156] (3) Glass transition temperature (Tg): Each of the barrier layer compositions prepared in Examples and Comparative Examples was irradiated with UV light at 400 mW / cm2 and 1,000 mJ / cm2 using a metal halide lamp, thereby preparing a sample having a thickness of 5 μm to 10 μm. For the prepared sample, tan δ according to temperature was measured using a dynamic mechanical analyzer (DMA) while the temperature was increased at a temperature increase rate of 5°C / min. Among the tan δ values ​​according to temperature, the temperature that provided the highest tan δ was defined as the glass transition temperature.

[0157] (4) Yellowness Index: The yellowness index is a value measured according to ASTM D 1925. Each of the barrier layer compositions prepared in Examples and Comparative Examples and disposed between release films (e.g., cycloolefin films) was irradiated with UV light using a metal halide lamp at 400 mW / cm2 and 1,000 mJ / cm2 to form a 10 μm thick layer, and then the yellowness index of the layer was measured using a colorimeter (CM3600A, KONICA-MINOLTA) in transmission mode at 25°C.

[0158] (5) Crack resistance: The crack resistance of the polarizing plate was evaluated under thermal shock conditions. The polarizing plate was cut into a size of 50 mm × 50 mm (length × width) and then laminated onto a glass sheet to prepare a sample. The sample was subjected to 250 cycles of heat treatment, each of which included heating the sample from -40°C to 85°C under certain conditions, in which the sample was allowed to stand at -40°C for 30 minutes before heating and at 85°C for 30 minutes after heating. The cracks generated on the polarizing plate on the MD were observed with the naked eye in the reflection mode and the backlight mode under fluorescent light. No cracks were rated as O, and even slight cracks were rated as X.

[0159] [Table 2]

[0160]

[0161] As shown in Table 2, the polarizing plate according to the present invention exhibits good adhesion to the polarizer and good barrier effect, and can prevent cracks from being generated in the polarizer under thermal shock conditions. In addition, the polarizing plate according to the present invention exhibits low peel strength after curing to make it easy to peel the treated film from the barrier layer, thereby inhibiting crack generation during peeling. In addition, even if the thioxanthone light enhancer is not included, the polarizing plate according to the present invention has a low yellow index, thereby preventing yellowing in the barrier layer.

[0162] In contrast, the polarizing plate of the comparative example prepared using the composition including the iodonium initiator or the sulfonium phosphate initiator exhibited poor crack resistance and high peel strength relative to the treated film.

[0163] It should be understood that various modifications, changes, alterations, and equivalent embodiments may be made by those skilled in the art without departing from the spirit and scope of the present invention.

Claims

1. A polarizing plate, comprising: An adhesive layer, a barrier layer, a polarizer, and a protective film stacked in the stated order, The barrier layer is directly formed on the polarizer and is formed of a barrier layer composition comprising a (meth)acrylate compound, an epoxy compound and a sulfonium antimony initiator, and The epoxy compound includes a difunctional alicyclic epoxy compound, wherein the (meth)acrylate compound comprises a hydrophilic (meth)acrylate compound, wherein the barrier layer composition further comprises at least one of a monofunctional aromatic epoxy compound and a difunctional aliphatic epoxy compound, the difunctional alicyclic epoxy compound and the at least one of the (meth)acrylate compound, the monofunctional aromatic epoxy compound and the difunctional aliphatic epoxy compound being present in a weight ratio of 60 wt % to 90 wt % of the difunctional alicyclic epoxy compound: 10 wt % to 40 wt % of the at least one of the (meth)acrylate compound, the monofunctional aromatic epoxy compound and the difunctional aliphatic epoxy compound, based on 100 parts by weight of the total, The difunctional aliphatic epoxy compound is present in an amount of 10 wt % to 40 wt % in terms of solid content in the curable component of the barrier layer composition. 2 . The polarizing plate according to claim 1 , wherein the barrier layer has a glass transition temperature of 90° C. or more. The polarizing plate according to claim 1 , wherein the barrier layer has a yellowness index of 1.0 or less.

4. The polarizing plate according to claim 1, wherein the sulfonium antimony initiator comprises at least one cation selected from triphenylsulfonium, diphenyl-4-thiophenoxyphenylsulfonium and diphenyl-4-phenylthienylsulfonium and at least one anion selected from hexafluoroantimonate and hexachloroantimonate. The polarizing plate according to claim 1 , wherein the barrier layer has a thickness of 20 μm or less.

6. A method for manufacturing a polarizing plate, comprising: depositing a barrier layer composition onto one surface of the polarizer and then attaching a treatment film thereto; as well as curing the barrier layer composition to form a barrier layer, and then peeling the treatment film from the barrier layer, wherein the barrier layer is formed of a barrier layer composition comprising a (meth)acrylate compound, an epoxy compound and a sulfonium antimony initiator, the epoxy compound comprises a bifunctional alicyclic epoxy compound, the (meth)acrylate compound comprises a hydrophilic (meth)acrylate compound, wherein the barrier layer composition further comprises at least one of a monofunctional aromatic epoxy compound and a difunctional aliphatic epoxy compound, the difunctional alicyclic epoxy compound and the at least one of the (meth)acrylate compound, the monofunctional aromatic epoxy compound and the difunctional aliphatic epoxy compound being present in a weight ratio of 60 wt % to 90 wt % of the difunctional alicyclic epoxy compound: 10 wt % to 40 wt % of the at least one of the (meth)acrylate compound, the monofunctional aromatic epoxy compound and the difunctional aliphatic epoxy compound, based on 100 parts by weight of the total, The difunctional aliphatic epoxy compound is present in an amount of 10 wt % to 40 wt % in terms of solid content in the curable component of the barrier layer composition, and The peel strength between the barrier layer and the treatment film is 40 gf / 25 mm or less. 7 . The method for manufacturing a polarizing plate according to claim 6 , wherein the processing film comprises a non-stretched or stretched polypropylene film, or a non-stretched or stretched polyethylene terephthalate film.

8. The method for manufacturing a polarizing plate according to claim 6, further comprising: An adhesive layer composition is deposited on one surface of a protective film and the protective film is attached to the other surface of the polarizer, and then the adhesive layer composition is cured.

9. An optical display comprising the polarizing plate according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Polarizer protective film and manufacturing method thereof, polarizing plate and manufacturing method thereof, and image display device

    JP2006220732A

  • System in sales agency and sales merchandise explanation support method

    JP2009122796A